Biomass-Derived from Bamboo Leaf Ash: Pozzolanic Reactivity - Moraes, M. J. B. [UNESP] (2018)
Bamboo leaf ash (BLA) was assessed as a pozzolanic material in pastes and mortars. Differently from most of research performed, the BLA studied in this paper was obtained through an auto-combustion process. This material was characterized by means of X-ray fluorescence, laser granulometry and powder X-ray diffraction. Pastes of calcium hydroxide/BLA in proportions of 1:1, 1:2 and 2:1 were assessed through thermogravimetric analysis after 7 days of curing. The compressive strength development of Portland cement mortars containing 20% of BLA cured during 3, 7 and 28 days at room temperature were compared with a control mortar (only Portland cement). The obtained results showed that BLA is an alternative pozzolanic material presenting high reactivity and can be used in the production of blended Portland cement mortars.